2015
DOI: 10.1111/cts.12285
|View full text |Cite
|
Sign up to set email alerts
|

Culturally Competent Strategies for Recruitment and Retention of African American Populations into Clinical Trials

Abstract: Purpose To identify successful recruitment strategies, challenges and best practices for researchers to engage African American communities in clinical studies taken into consideration target participants’ culture and context. Methods We reviewed 50 studies conducted from 2001-2012 at an inner-city research center to determine the type, duration, anticipated enrollments and actual enrollments. Survey was sent to study coordinators to obtain data on recruitment and retention strategies, challenges and dropout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
146
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(154 citation statements)
references
References 18 publications
6
146
2
Order By: Relevance
“…9,[16][17][18][19] A review of 50 studies of AAs in clinical trials identified barriers to retention including lack of a study partner, lower educational level, and lack of compensation. 20 An earlier study conducted by our team found that a decentralized CBPR approach led to intervention…”
Section: Methodsmentioning
confidence: 95%
“…9,[16][17][18][19] A review of 50 studies of AAs in clinical trials identified barriers to retention including lack of a study partner, lower educational level, and lack of compensation. 20 An earlier study conducted by our team found that a decentralized CBPR approach led to intervention…”
Section: Methodsmentioning
confidence: 95%
“…However, there is very little research on how to effectively reduce these disparities in study recruitment and design, and once reduced, how to prevent attrition among historically underrepresented groups over long follow-up periods. 7 Further, there is no evidence race alone is a determining factor in compliance and attrition rates. 8 Other elements such as socioeconomic status, cultural background, age, study design, and the study investigators may all play a role in initial participation and retention across races.…”
Section: Attrition Differences In Aric -George Et Almentioning
confidence: 99%
“…A meta-analysis of 24 clinical trials that included African American participants, with follow-up times ranging from 3 months to 5 years (median of 34 months), had an average drop-out rate of 23.3%. 7 Reasons for drop-out included personal obligations, loss to follow-up, non-compliance with study requirements, and monetary or other incentives for participation that participants considered too low. 7 Retention strategies reported were similar to those used in ARIC and focused on building rapport with participants and maintaining frequent, thoughtful communication while trying to keep the burden of participation low.…”
Section: Attrition Differences In Aric -George Et Almentioning
confidence: 99%
See 2 more Smart Citations